Molecular Biology Can Change the Classic Laboratory Approach for Intestinal Protozoan Infections - Formenti, Fabio; Valerio, Matteo; Guerriero, Massimo; Perandin, Francesca; Pajola, Barbara; Mistretta, Manuela; Tais, Stefano; Degani, Monica; Bisoffi, Zeno (Frontiers in Microbiology, 2017)
For many years microscopy has been considered the mainstay of the diagnosis of parasitic infections. In our laboratory, before the advent of molecular biology, the approach for the identification of parasitic infections in stools was the microscopic exam of three samples. Once we adopted molecular biology, a real-time PCR on one single sample was added to the classical coproparasitological exam of three samples. Given the high sensitivity of real-time PCR (Rt-PCR), we then decided to evaluate if a change of our routine was justified. In detail, we intended to assess if a much more practical routine, based on the analysis of a single faecal sample, was sufficiently sensitive to replace the routine described above. The new approach to be evaluated included, on the same and unique faecal sample, a classical coproparasitological exam plus Rt-PCR. The data obtained showed that the sensitivity of the new proposed approach remains very high, despite the reduction of coproparasitological exams from three to one, with the advantage of reducing costs and saving time, both for patients and for the laboratory.